A Potent Antibiotic Combination of Linezolid and Polymycin B Nonapeptide Against Klebsiella pneumoniae Infection In Vitro and In Vivo - Huang, Ting; Lv, Zheng; Lin, Jiafu; Zhao, Kelei; Zhai, Longfei; Wang, Xinrong; Chu, Yiwen (Frontiers in Pharmacology, 2022)
The emergence of antibiotic resistant Gram-negative bacteria such as Klebsiella pneumoniae (KP) is becoming a major public health threat and imposing a financial burden worldwide. A serious lack of new drugs under development is undermining efforts to fight them. In this study, we report a potent combination of linezolid and polymyxin B nonapeptide PBNP (LP) against KP infection in vitro and in vivo. The checkerboard test and the time-kill assay were performed to detect the antibacterial activity of LP against KP in vitro. And the Caenorhabditis elegans (C. elegans) was used as infection model to evaluate the protective effect of LP against KP infection in vivo. The LP combination showed significantly synergistic activity and antibacterial effects against KP, while linezolid and PBNP as monotherapies revealed no dramatically antibacterial activity against the KP strains. Additionally, we found that the LP treatment altered the biofilm production and morphology of KP. Furthermore, the LP treatments significantly protected C. elegans from KP infection. In conclusion, this study indicated that the LP combination exhibited significantly synergistic activity against KP and PBNP can be used as a potential activity enhancer. More importantly, this strategy provided the improvement of antibacterial activity spectrum of agents like linezolid and represented a potent alternative to overcome antibiotic resistance in the future.